ANALYSIS OF WOMEN'S REPRESENTATION IN POLITICAL POSITIONS OF LEADERS OF DPRD IN BULUNGAN REGENCY - Wempi Feber; Iskandar Iskandar (DIA: Jurnal Administrasi Publik, 2022)
This study aims to determine the description of women's representation in political positions, especially in the current political positions of the DPRD (Regional People's Representative Assembly) leadership in Bulungan Regency and to find out what factors influence women's representation in political positions led by DPRD in Bulungan Regency and to find out the obstacles faced by women in political positions, leadership of the DPRD in Bulungan Regency. (Study of the Leadership of the Bulungan Regency DPRD for the 2019-2024 Period). The informants in this study consisted of the chairman of the DPRD, the secretary of the DPRD, members of the DPRD, the chairman of the KPUD (Regional Election Commission), the secretary of the KPUD, members of the KPUD, and the community who were chosen randomly without regard to the existing strata. According to the type of data used and the level of explanation, this research is a descriptive qualitative research type. While the research data analysis using an interactive analysis model which consisted of three main things in analyzing the data, namely: data reduction, data presentation, and conclusion drawing/verification. Based on the results of the analysis of the results of the research conducted, it is known that quantitatively, the involvement of women in political positions in the Bulungan Regency is still lacking. This can be seen from the existing data and the results of interviews with various informants who are involved in political positions and those who are not involved. As can be seen from the data, there are only 4 women who hold the position of DPRD members out of 25 members. The obstacles for women in political positions are caused by several factors such as the level of education and political understanding is still very lacking, organizational experience and self-confidence are still lacking, and financial factors.